Evaluation of Turkish propolis for its chemical composition, antioxidant capacity, anti-proliferative effect on several human breast cancer cell lines and proliferative effect on fibroblasts and mouse mesenchymal stem cell line - Ozdal, Tugba; Sari-Kaplan, Gulce; Mutlu-Altundag, Ergul; Boyacioglu, Dilek; Capanoglu, Esra (Taylor & Francis Ltd, 2018)
Propolis is an extremely complex resinous natural compound collected by honey bees from various plant sources and exhibits pharmacological and biological properties attributed to the presence of polyphenols. This study examined the total phenolic and flavonoid contents as well as the total antioxidant capacity using 2,2 '-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS), 2,2-diphenyl-1-picrylhydrazyl (DPPH), cupric-reducing antioxidant capacity (CUPRAC), and ferric-reducing antioxidant power (FRAP) methods. Turkish propolis has very high total phenolic (314.36 +/- 3.65 mg GAE/g propolis) and total flavonoid contents (522.71 +/- 11.45 mg QE/g propolis). The highest antioxidant capacity value was obtained by the CUPRAC method (1184.94 +/- 63.27 mg TE/g propolis). Phenolic profile of Turkish propolis was also determined by high performance liquid chromatography with photodiode array detection (HPLC-PDA) method. The main phenolic compounds identified in Turkish propolis was flavonoids including pinocembrin > chrysin > galangin > pinobanksin > pinostrobin and phenolic acids including caffeic acid > p-coumaric acid > ferrulic acid > t-cinnamic acid. In the present work, anti-proliferative and proliferative effects of propolis extracts were also investigated on two different breast cancer cell lines; MDA-MB-231, UACC-3199 and on two normal cell lines; fibroblasts and mouse mesenchymal stem cell lines. According to the XTT results, Turkish propolis sample showed significant anti-proliferative effect on MDA-MB-231 and UACC breast cancer cell lines. Interestingly, Turkish propolis sample had proliferative effect on both fibroblasts and mouse mesenchymal stem cells. These results suggest that Turkish propolis can be considered as a potent agent on breast cancer treatment for further investigations.
Keywords: propolis; antioxidant capacity; phenolic profile; HPLC-PDA; breast cancer cell line; mesenchymal stem cell line